Utilization of Bottom Ash as an Adsorbent for Color and COD Removal for Textile Industry Waste - Pricilla Jihan Fadilla; Mohamad Rangga Sururi; Dyah Marganingrum; Mila Dirgawati (Universitas Diponegoro, 2022)
This study investigates the use of bottom ash as an adsorbent with and without chemical activation treatment. This study also determines the effect of pH and stirring speed on the efficiency of bottom ash in the adsorption of color and COD. Bottom ash was ground and sieved by 100 mesh sieves and was activated by hydrochloric acid 2%. The experiments were conducted at pH variations of 6, 8, 10; contact time variations of 30, 60, and 90 minutes; and stirring speeds of 30 and 60 rpm. The most effective adsorption by non-activated adsorbents occurred at the combination of pH six and stirring speed of 60 rpm with the removal efficiency for color 66.30% at a contact time of 90 minutes and for COD 31.55% at a contact time of 30 minutes. While for activated adsorbent, the highest removal for color (77.44%) and COD removal (40.54%) were at pH 6, stirring speed 30 rpm, contact time 30 minutes. The bottom ash was potentially used as an adsorbent for treating wastewater containing high concentrations of color and COD.